Early menopause and type 2 diabetes: A cross-sectional study at Royal Prima Hospital - Waren, N Wignes; Wijaya, Johanna Fransisca; Dalimunthe, Siti Aisyah; Kuswani, Lili; Riskaldy, Riskaldy; Munadi, Munadi (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Type 2 diabetes mellitus (T2DM) is a metabolic disease affecting various organs and causing hormonal disorders. Estrogen deficiency can alter a woman's menstrual cycle and trigger menopause, which affects reproductive health, fat distribution, lipid profiles, and the nervous system. This study aimed to assess the relationship between T2DM and menopausal age in women in the menopausal phase. The research method used was observational with a cross-sectional design, using 120 medical records of menopausal women from the period 2020-2022 at the Royal Prima Hospital. To explore the relationship between menopausal age and T2DM, bivariate analysis was performed, including the Chi-square test or Fisher's Exact Test for categorical variables, as well as t-test or Mann-Whitney U test for numerical variables. The results showed that the age range of 51-60 years constituted the largest group of 120 T2DM patients (29.17%). The most common age of onset of menopause was between 46-50 years, and showed a significant influence on the risk of T2DM (sig value 0.026 and t value 2.257). Blood pressure, which varied from 81 mmHg to 283 mmHg, showed no significant association with T2DM. It can be concluded that age at the onset of menopause was significantly associated with the risk of T2DM, whereas blood pressure had no significant effect on T2DM in this study. These findings highlight the importance of health monitoring in women with early menopause to prevent the development of T2DM.